Rhodium(II)-catalyzed transannulation of 1-sulfonyl-1, 2, 3-triazoles with 2H-azirines: a new method to dihydropyrazines. Issue 3 (14th January 2015) - Ding, Haixin; Hong, Sanguo; Zhang, Ning
Graphical abstract